2017
DOI: 10.1177/2325967117694025
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Impact of Abdominal Oblique Injuries in Major and Minor League Baseball

Abstract: Background:Oblique injuries are known to be a common cause of time out of play for professional baseball players, and prior work has suggested that injury rates may be on the rise in Major League Baseball (MLB).Purpose:To better understand the current incidence of oblique injuries, determine their impact based on time out of play, and to identify common injury patterns that may guide future injury prevention programs.Study Design:Descriptive epidemiological study.Methods:Using the MLB Health and Injury Trackin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 15 publications
1
58
3
Order By: Relevance
“…Another potential reason could be reticence of MiLB players to undergo surgery because of a strong desire to minimize time out of play as they attempt to move forward in the system. In contrast to many previous reports on rising injuries in baseball, 3,5,7,12 the overall burden of HBP injuries has remained fairly steady across all of baseball. The greatest number of injuries was reported in 2011 (n = 648), and the lowest occurred the following year (n = 532).…”
Section: Discussioncontrasting
confidence: 66%
“…Another potential reason could be reticence of MiLB players to undergo surgery because of a strong desire to minimize time out of play as they attempt to move forward in the system. In contrast to many previous reports on rising injuries in baseball, 3,5,7,12 the overall burden of HBP injuries has remained fairly steady across all of baseball. The greatest number of injuries was reported in 2011 (n = 648), and the lowest occurred the following year (n = 532).…”
Section: Discussioncontrasting
confidence: 66%
“…Their incidence has been found to increase significantly, and it has been reported that between 25 and 33% of all MLB pitchers have had an MUCL reconstruction surgery at some point during their baseball careers [4•, 44, 45, 48]. Research has also been conducted to further characterize other clinically relevant injuries such as abdominal oblique injuries, lumbar spine injuries, and sliding-related injuries [49][50][51].…”
Section: Epidemiologymentioning
confidence: 99%
“…The HITS database has proven to be an excellent source for epidemiologic studies involving injuries in baseball, such as recent studies on abdominal oblique injuries, sliding injuries, elbow injuries, and hamstring strains. 1 , 5 , 6 , 9 …”
Section: Methodsmentioning
confidence: 99%